2013
DOI: 10.1371/journal.pone.0054475
|View full text |Cite
|
Sign up to set email alerts
|

Structural Brain Changes in Chronic Pain Reflect Probably Neither Damage Nor Atrophy

Abstract: Chronic pain appears to be associated with brain gray matter reduction in areas ascribable to the transmission of pain. The morphological processes underlying these structural changes, probably following functional reorganisation and central plasticity in the brain, remain unclear. The pain in hip osteoarthritis is one of the few chronic pain syndromes which are principally curable. We investigated 20 patients with chronic pain due to unilateral coxarthrosis (mean age 63.25±9.46 (SD) years, 10 female) before h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(106 citation statements)
references
References 43 publications
(88 reference statements)
5
99
0
2
Order By: Relevance
“…To date, the causality of chronic pain and associated brain changes remains largely unknown. Previous study findings (Rodriguez-Raecke et al 2009, 2013; Seminowicz et al 2011) support the notion that morphometric brain changes occur as a result of the chronic pain. As such, patients may be more or less resilient to a chronic pain state.…”
Section: Discussionsupporting
confidence: 79%
“…To date, the causality of chronic pain and associated brain changes remains largely unknown. Previous study findings (Rodriguez-Raecke et al 2009, 2013; Seminowicz et al 2011) support the notion that morphometric brain changes occur as a result of the chronic pain. As such, patients may be more or less resilient to a chronic pain state.…”
Section: Discussionsupporting
confidence: 79%
“…Previous findings in chronic pain patients demonstrated that pain-related gray matter changes are not static and at least partially reversible after successful treatment of pain. [41][42][43] Potential limitations of the present study include the cross-sectional character and the use of questionnaire data to assess fear and potential avoidance of physical activity. Therefore, future studies including longitudinal designs and objective measures of physical activity such as activity monitors are warranted to gain further insights into the dynamics of GMV changes in relation to activity avoidance in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…105 An additional study by Rodriguez-Raecke and colleagues monitored changes in brain morphometry in 20 patients with chronic pain due to hip osteoarthritis who underwent hip replacement. 125 When compared with controls preoperatively, patients with chronic pain were shown to have significantly less gray matter in the ACC, the insular cortex and operculum, the orbitofrontal cortex, and the dorsolateral prefrontal cortex, which corresponded to duration of pain. At the postoperative time point when the patients reported being pain free, an increase in gray matter was observed in the same area, suggesting that these changes may be at least partially reversible with appropriate analgesia.…”
Section: Neuroimaging Of Chronic Painmentioning
confidence: 97%